Emotional Intelligence and Motivation as Predictors of Lower Secondary School Students’ Mathematics Achievement - Fathrul Arriah; Abd. Kadir Jaelani; Ilhamuddin Ilhamuddin; Ahmad Syamsuadi; Ririn Anggraeni (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Emotional intelligence (EI) and learning motivation are widely recognized as critical non-cognitive factors influencing academic success. However, empirical evidence regarding their impact on mathematics achievement within Indonesian Secondary School contexts remains limited. This study examines the individual and simultaneous effects of EI and learning motivation on mathematics learning outcomes among Grade VIII students. Utilizing an ex-post facto quantitative design, a saturated sampling technique was employed to select all 50 Grade VIII students from Lower Secondary School 12 Bulukumba, South Sulawesi, Indonesia. Data was collected via a validated mathematics achievement test and two Likert-scale questionnaires assessing EI and motivation. Descriptive and inferential statistical analyses, including multiple linear regression, were performed using SPSS. Descriptive results categorized student EI as high (M=51.62, SD=4.34), learning motivation as high (M=53.60, SD=6.66), and mathematics outcomes as moderate (M=75.80, SD=10.90). Inferential analysis revealed that EI significantly predicted mathematics outcomes (R2 = 0.14, p = 0.008), and learning motivation emerged as a stronger individual predictor (R2 = 0.302, p<0.001). Simultaneously, both variables exerted a significant combined effect, explaining 39.2% of the variance (R2 = 0.392, p<0.001). These findings underscore the critical role of affective factors in STEM education, suggesting that integrating socio-emotional development programs into secondary mathematics instruction can significantly enhance student performance.